2007
DOI: 10.1016/j.ymeth.2006.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical analyses of transcriptional regulatory mechanisms in a chromatin context

Abstract: We have optimized a recombinant chromatin assembly system that properly incorporates core histones and histone H1 into a chromatin template containing a natural promoter sequence. This article provides a step-by-step procedure for expression and purification of the proteins required for assembling well-defined chromatin templates. We describe how the degree of chromatin assembly in the absence and presence of histone H1 is measured using topological analysis and the use of micrococcal nuclease digestion perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Assembly was performed at a 4:7 histone:DNA mass ratio. The degree of assembly was confirmed by micrococcal nuclease digestion (26). Micrococcal nuclease digestion of the chromatin-assembled 4TxRE promoter template is shown by Sharma et al (44).…”
Section: Methodsmentioning
confidence: 84%
See 2 more Smart Citations
“…Assembly was performed at a 4:7 histone:DNA mass ratio. The degree of assembly was confirmed by micrococcal nuclease digestion (26). Micrococcal nuclease digestion of the chromatin-assembled 4TxRE promoter template is shown by Sharma et al (44).…”
Section: Methodsmentioning
confidence: 84%
“…For these studies, we assembled the Tax-responsive promoter fragment used in Fig. 1 into chromatin, using purified Drosophila core histones and the recombinant assembly proteins Acf1/ISWI and Drosophila NAP-1 (14,26,34). Micrococcal nuclease assays were performed to verify the assembly of nucleosomes on the immobilized promoter fragment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies on in vitro reconstitution of yeast and mammalian nucleosomes suggested that mammalian nucleosomes bind DNA more readily (80% chromatin assembly), and that yeast nucleosomes are comparatively unstable (~16% assembly) (Lee et al, 1982). Furthermore, it has long been known that in vitro transcription using human chromatin (or any higher eukaryote chromatin) inhibits transcription (Konesky and Laybourn, 2007; Lorch et al, 1987), but a recent paper using native yeast chromatin showed enhanced in vitro transcription compared to naked DNA (Nagai et al, 2017). Our study may provide a means to reconcile these opposing observations.…”
Section: Discussionmentioning
confidence: 99%
“…The assembled chromatin was stored in a buffer containing 0.1 M NaCl, 0.1% Nonidet P-40, 10 mM Tris-HCl (pH 7.5), 1 mM EDTA, 5 mM DTT, and 20% glycerol at 4°C. Micrococcal nuclease assays were performed as described (34).…”
Section: Methodsmentioning
confidence: 99%